Effects of renewable energy on landscape in Europe: Comparison of hydro, wind, solar, bio-, geothermal and infrastructure energy landscapes - Frolova, Marina; Centeri, Csaba; Benediktsson, Karl; Hunziker, Marcel; Kabai, Robert; Scognamiglio, Alessandra; Martinopoulos, Georgios; Sismani, Georgia; Brito, Paulo; Muñoz-Cerón, Emilio; Słupiński, Mateusz; Ghislanzoni, Michela; et al. (Hungarian Geographical Bulletin, 2019)
Landscape quality has become a fundamental issue in the development of renewable energy (henceforth abbreviated RE) projects. Rapid technological advances in RE production and distribution, coupled with changing policy frameworks, bring specific challenges during planning in order to avoid degradation of landscape quality. The current work provides a comprehensive review on RE landscapes and the impacts of RE systems on landscape for most European countries. It is based on a review by an interdisciplinary international team of experts of empirical research findings on landscape impacts of RE from thirty-seven countries that have participated in the COST Action TU1401 Renewable Energy and Landscape Quality (RELY).